Ada & Zangemann : a tale of software, skateboards, and raspberry ice cream - Kirschner, Matthias (No Starch Press, 2022)
"Ada, a curious tinkerer, starts to experiment with hardware and software and, in the process, realizes how important it is for her and others to control technology"--